Respostas
respondido por:
2
(3 - y^ -2)+(2y^2 + 1y + 1)
2 3 4 2
mmc(2,3,4) = 12
(3 - y^ -2)+(2y^2 + 1y + 1)
2 3 4 2
18 - 12y^2 - 24 + 8y^2 + 3y + 6
- 4y^2 + 3
respondido por:
1
(3/2-y)²+(2/3y²+1/4y+1/2)
3/2²-2.3/2.y+y²)+(2/3y²+1/4y+1/2)
9/4-3y+y²+2/3y²+1/4y+1/2
y²+2/3y²-3y+1/4y+9/4+1/2
mmc=12
12y²+8y²-12y+3y+27+6
20y²-9y+33=0
Δ=(-9)²-4.20.33
Δ=81-2640
Δ=-2559Ф
3/2²-2.3/2.y+y²)+(2/3y²+1/4y+1/2)
9/4-3y+y²+2/3y²+1/4y+1/2
y²+2/3y²-3y+1/4y+9/4+1/2
mmc=12
12y²+8y²-12y+3y+27+6
20y²-9y+33=0
Δ=(-9)²-4.20.33
Δ=81-2640
Δ=-2559Ф
Perguntas similares
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás